Are They Going to Stay? Attending to Emotions in Nonformal Settings - Edward W. Taylor (Adult Education Research Conference, 2008)
Emotions play a key role in teaching in nonformal educational settings. Understanding the nature of this relationship and developing an awareness of learner emotions while teaching in nonformal settings is an essential practice for the nonformal educator.
Keywords: nonformal education; emotions; teaching